Judicial response to the representative parties rule in England and Australia - Seymour, J (2001)
Use of the representative parties rule in England and Australia has been stifled by restrictive interpretation of the circumstances in which it is available. Chapter 1 demonstrates that the predominant test in England for the 'same interest' required by the rule would, if consistently applied, defeat any claim to use the rule. The recent change of test in Australia widens the rule's potential scope but does not appear to have resulted in significantly more liberal interpretation. Chapter 2 discusses the rule's operation, including res judicata, the enforcement of judgments, and the protection of the interests of those represented and of the named parties. It concludes that the rule diverges from the traditional model of individual voluntary civil litigation, and is characterised by uncertainty. Chapter 3 argues that this uncertainty may have encouraged a defensive posture by the courts, limiting use of the rule and avoiding the need to address those issues which demand resolution. Chapter 4 notes that various features of the rule undermine a number of principles commonly associated with procedural fairness. It is argued that judicial response to these features often pays insufficient attention to two issues. The first is whether the purpose which the principle is expected to promote is in fact protected by the rule, even if the principle itself is undermined. The second is the need to balance the rule's limitation of some principles against its particular benefits. It is further argued that some successful representative claims exemplify circumstances in which the primary purpose of procedural law (accurate application of the substantive law) is served by the rule. Chapter 5 identifies other successful representative claims, particularly against representatives of the members of unincorporated associations, which, it is argued, ought to be viewed not as supporting accurate application, but rather as facilitating development, of the substantive law.